Aerial infrared photography used in evaluating peat bogs for Sphagnum moss - BARRY BANNATYNE (Canadian Institute of Mining, Metallurgy and Petroleum, 1984)
Ombrotrophic Sphagnum peat bogs have a characteristic signature on both colour injrared film (750 nm to 3,000 nm response) and Daedalus injrared line-scanner images (thermal infrared 3 to 5 microns and 8 to 14 microns response). This remote sensing method was used to survey bogs in southeast Manitoba to delineate targets for surface exploration. Target bogs all have a surface growth of Sphagnum; underlying dead Sphagnum ranges from 1 to 6 m thick. Large Sphagnum reserves exist in the Caribou cluster of bogs, and in /979 a bog first identified by infrared sensing was brought into production.